Genome wide analysis of recurrent parent genome recovery in different backcross populations for blast resistance through SSR markers in rice - Abro, Tanweer Fatah; Yusop, Mohd Rafii; Soomro, Zahoor Ahmed; Baloch, Abdul Wahid; Shar, Piar Ali; Gilal, Arfan Ahmed; Chattha, Shakeel Hussain; Ahmed Qureshi, Naeem; Ahmed Otho, Sohail (Pakistan Botanical Society, 2019)
Marker-assisted backcross breeding technique has been widely applied for incorporation of blast resistance genes into rice varieties. The monitoring of resistance genes along with recovery of recurrent parent is an essential aspect for reducing the donor genome content in backcross population. Current research was conducted to determine the recovery of recurrent parent in each backcross population of rice. Malaysian high yielding but blast susceptible rice variety MR219 was taken as recurrent parent while PongsuSeribu 2 was donor parent. Microsatellite markers commonly called as Simple sequence repeat markers were used to estimate recovery of recurrent parent genome i.e. MR219 in early generation of backcross population. A total of 300 microsatellite markerswere randomly applied on 12 rice chromosomes. 72 SSR markers found distinct and clear polymorphic between the parent PongsuSeribu 2 and MR219. These 72 polymorphic markers were utilized to analyze the recovery of plants in further subsequent generations. The background recovery ranged from 73-93.9% and 79- 96.3% in BC1F1 and BC2F1 generation. The proportion of recurrent parent genome increased and donor genome content decreases after every backcross generation. The recovery of recurrent parent genome content ranged from 94-97.1% in the selected improved advance lines of BC2F2 generation. In the advance lines, the average percent for the proportion of recurrent parent genome was 96.16%. Marker-assisted backcrossing efficiently accelerated the recurrent parent genome recovery within few backcrosses, reduced the backcross generation and saved plenty of time to intogress the genes against blast disease. The present results will be helpful for rice breeders for selecting true blast resistant lines along with maximum resemblance with recurrent parent.